Mechanism and optimization of non-thermal plasma-activated water for bacterial inactivation by underwater plasma jet and delivery of reactive species underwater by cylindrical DBD plasma - Tanitta Royintarat (2019)
© 2019 Korean Physical Society Plasma-activated water (PAW) has been in use for the past decade in sanitization against bacteria and other microorganisms. This research study compared PAW generated by a DC positive flyback transformer (FBT) underwater plasma jet with delivery of reactive species underwater by cylindrical dielectric barrier discharge (C-DBD) with a neon transformer. A Box–Behnken design was adopted as a response surface methodology (RSM) to design the experimental plan and optimize operating parameters including time, gas flow, and gas ratio. The physical responses comprise optical emission spectroscopy (OES), pH, oxidation-reduction potential (ORP), and electrical conductivity (EC). The chemical responses consist of hydrogen peroxide (H2O2) and hydroxyl radicals (OH·). The biological responses include Escherichia coli reduction and Staphylococcus aureus reduction. The optimal condition for underwater plasma jet was found to be Ar gas with a flow rate of 3 slm for 6.5 min of treatment time, which can reduce E. coli and S. aureus to 7.14 ± 0.14 and 3.10 ± 0.26 in log, respectively. Also, the optimal condition for delivery of reactive species underwater by C-DBD plasma was found to be Ar (99%): O2 (1%) gas mixture with an Ar gas flow rate of 4 slm for a treatment time of 11.5 min, which could reduce E. coli and S. aureus to 0.45 ± 0.07 and 2.45 ± 0.23 in log, respectively.